2019
DOI: 10.1111/jan.14153
|View full text |Cite
|
Sign up to set email alerts
|

The association between alexithymia, emotional intelligence and burnout among nursing assistants working in nursing home settings: A cross‐sectional study

Abstract: Aims To determine the explanatory power of alexithymia and emotional intelligence over burnout and to examine their combined explanatory capacity over burnout in the context of older adult care. Design Cross‐sectional. All participants voluntarily and anonymously completed a questionnaire survey. They were all blind to the aim of the study. Methods One hundred and fifty‐nine nursing assistants recruited during 2014 took part in the study. They belong to 10 nursing homes in the north of Spain. Sociodemographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…One person’s stable personality trait 14 that might be a factor contributing to burnout among medical students is alexithymia, which has been defined by difficulties in identifying and describing feelings, difficulty in distinguishing between the bodily sensations of emotional arousal and feelings, and restrictions regarding imagination and externally oriented thinking. 15 Many studies confirm that alexithymia is a risk factor for burnout among works, 16 such as in healthcare professionals 17 and nursing assistants, 18 alexithymia was also found to be associated with the components of burnout, such as depersonalization. 19 However, few studies have focused on the relationship between alexithymia and burnout among students.…”
Section: Introductionmentioning
confidence: 99%
“…One person’s stable personality trait 14 that might be a factor contributing to burnout among medical students is alexithymia, which has been defined by difficulties in identifying and describing feelings, difficulty in distinguishing between the bodily sensations of emotional arousal and feelings, and restrictions regarding imagination and externally oriented thinking. 15 Many studies confirm that alexithymia is a risk factor for burnout among works, 16 such as in healthcare professionals 17 and nursing assistants, 18 alexithymia was also found to be associated with the components of burnout, such as depersonalization. 19 However, few studies have focused on the relationship between alexithymia and burnout among students.…”
Section: Introductionmentioning
confidence: 99%
“…In a few studies, A study of 95 nurses in Greece by Aikaterini Moulou et al found that alexithymia was positively associated with depersonalization and emotional exhaustion in burnout and could influence overall burnout scores through personal achievement and family support. After investigating 159 nursing assistants in 10 nursing homes in northern Spain, Erkuden Aldaz et al found that, after strictly controlling the mixed effect of work characteristics, alexithymia made a moderate contribution to the depersonalization and personal accomplishment dimensions of burnout [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emergency health professionals are constantly faced with urgent situations and highrisk interventions, which frequently leads to burnout syndrome [1,2]. Burnout syndrome has often been linked to emotional intelligence, especially in healthcare staff [3,4]. Emotional intelligence is a significant predictor of low burnout [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Burnout syndrome has often been linked to emotional intelligence, especially in healthcare staff [3,4]. Emotional intelligence is a significant predictor of low burnout [3,5,6].…”
Section: Introductionmentioning
confidence: 99%